CAUSALITY FOREIGN DIRECT INVESTMENT ON GROSS DOMESTIC PRODUCT IN INDIA - ,SE, Andrian (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Foreign Direct Investment is one of typeÂ investment, that is one of the sources of a nation's economy, because of ability to create labour market and transfer technology. This study aims to determine the relationship between foreign Direct Investment (FDI) andÂ Gross Domestic Product (GDP) in India.Using the data of FDI and GDP on 1980-2014 periods, and method of causality, this study tried to examine FDI causes GDP or whether GDP causes FDI. To examine the relationship between two variables, there are three steps test conducted, unit roots test (using the ADF test); co integration test (using the Johansen co integration test); and causality test (using the Granger Causality test). Conclusion indicated that FDI influence GDP.Keywords : Foreign Direct Investment (FDI), Gross Domestic Product (GDP), Granger Causality, India